Corneal Subbasal Nerve Recovery in an Acute Case of Ultraviolet Keratitis Treated with Autologous Serum Eye Drops - Farshad Abedi; Pedram Hamrah (Journal of Ophthalmology)
Purpose. To report degeneration of subbasal corneal nerves and the subsequent neuroregeneration in a case of acute ultraviolet (UV) keratitis, treated with autologous serum eye drops. Methods. Case report. Results. A 37-year-old female presented with ocular discomfort and blurred vision in both eyes, after exposure to UV-C light in a laboratory. On exam, she had bilateral conjunctival injection and superficial punctate keratitis (SPK), worse in the left, consistent with acute, bilateral, but asymmetric UV-C keratitis. She was initially started on antibiotic ointment and lubricant eye drops. On her follow-up visit 3 days later, corneas had persistent SPK bilaterally. Laser scanning in vivo confocal microscopy (IVCM) showed beading of subbasal corneal nerves in the right eye and decreased subbasal corneal nerve density and numerous amputated nerves in the left eye. Autologous serum eye drops 20%, eight times a day, and loteprednol 0.5% ophthalmic solution were commenced in both eyes. Twelve weeks later, her symptoms fully resolved; IVCM revealed near-normal subbasal corneal nerve density in both eyes. Conclusions. IVCM demonstrated dramatic damage to subbasal corneal nerves after brief UV-C exposure. The patient, treated with autologous serum eye drops in both eyes, achieved resolution of symptoms and recovery of subbasal corneal nerves.